2020
DOI: 10.1152/ajpcell.00072.2020
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization leads to alterations in intracellular phosphagen and creatine transporter content in human skeletal muscle

Abstract: The role of dysregulated intracellular creatine (Cr) metabolism in disuse atrophy is unknown. In this study, skeletal muscle biopsy samples were obtained after 7 days of unilateral leg immobilization (IMMOB) and from the nonimmobilized control limb (CTRL) of 15 healthy men (23.1 ± 3.5 yr). Samples were analyzed for fiber type cross-sectional area (CSA) and creatine transporter (CreaT) at the cell membrane periphery (MEM) or intracellular (INT) areas, via immunofluorescence microscopy. Creatine kinase (CK) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Previous research has identified reductions in intracellular phosphagen and glycogen content following muscle disuse [135]. More recently, it was discovered that periods of muscle disuse also resulted in alterations in intracellular phosphagen and creatine transporter content in human skeletal muscle, demonstrating how the cell adapts to the aforementioned metabolic disruptions in cellular energy turnover [136]. These alterations in intracellular phosphate and transporter protein content, coupled with mitochondrial-mediated apoptosis, highlight a rationale for the potential therapeutic benefit of creatine supplementation to attenuate reductions in phosphagen levels associated with muscle disuse.…”
Section: Immobilization and Muscle Dysfunctionmentioning
confidence: 99%
“…Previous research has identified reductions in intracellular phosphagen and glycogen content following muscle disuse [135]. More recently, it was discovered that periods of muscle disuse also resulted in alterations in intracellular phosphagen and creatine transporter content in human skeletal muscle, demonstrating how the cell adapts to the aforementioned metabolic disruptions in cellular energy turnover [136]. These alterations in intracellular phosphate and transporter protein content, coupled with mitochondrial-mediated apoptosis, highlight a rationale for the potential therapeutic benefit of creatine supplementation to attenuate reductions in phosphagen levels associated with muscle disuse.…”
Section: Immobilization and Muscle Dysfunctionmentioning
confidence: 99%
“…In contrast to the complexity of interacting pathways involved in cancer-related cachexia, the key changes associated with sarcopenia included the downregulation of pathways related to energy metabolism, namely the phosphagen metabolic system, gluconeogenesis pathway, and the proton-transporting ATP synthase activity, among others ( Figure 4 A). In a study investigating the role of dysregulated intracellular creatine metabolism in disuse muscle, Luo et al demonstrated that seven days of unilateral limb immobilization resulted in greater intracellular creatinine transporter and reduced phosphocreatine content when compared with the non-immobilized control limb in a cohort of 15 healthy men; they hypothesized that the lower intramuscular phosphocreatine content observed might be explained by the significantly lower fast-twitch fiber cross-sectional area compared with the control biopsies from the non-immobilized limb [ 65 ]. Sarcopenia and aging have been associated with the preferential atrophy of fast-twitch fibers and a glycolytic-to-oxidative metabolic shift [ 39 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Creatine is an energetic compound able to induce the recycling of adenosine triphosphate (ATP) in skeletal muscle tissue. It can have a beneficial role during immobilization-induced muscle disuse in humans [ 179 , 180 ]. Alongside amino acids, vitamins also play an essential role in the prevention of muscle atrophy characterized by an increase in oxidative stress and a decrease in the production of endogenous antioxidant species.…”
Section: Potential Drugs and Natural Compounds As Pharmacological Cou...mentioning
confidence: 99%